تأثير أزمة جائحة كوفيد-19 على الأمن الغذائي في الجزائر - عبد الله الحاج, سليم (University of Eloued جامعة الوادي, 2024)
Abstract: This research paper aims to study how the Global Food Security was affected the COVID-19 pandemic crisis with a focus on Algeria, therefore it highlights the status of Food Security within the pandemic response policies and the measures taken in this regard in order to maintain stability. As the dynamics of the crisis posed a clear threat to the pillars of Food Security due to its severe nature (crisis) , which left various economic , social and security effects that negatively affected the availability and consumption factors , specific to the country’s ability to ensure that their own needs are met in a balanced manner. In this context, Algeria is working to achieve self-sufficiency as the crisis came to test its aptitude to adapt the response to exceptional challenges with its plans and aspirations to modernize economy and promoting the national production , and in order to preserve Food Security during the crisis of Covid-19 , Algeria has introduced some measures such as combating the phenomenon of illegal speculation and supporting the internal consumption to ensure that the population obtains its needs in light of the difficult conditions imposed by the pandemic ,which constitute valuable data for entering future prospects. تعالج هذه الورقة البحثية موضوع الأمن الغذائي ومدى تأثره بأزمة جائحة كوفيد-19 على المستوى الدولي مع التركيز على الحالة الجزائرية، حيث تهدف الى تسليط الضوء على مكانة الامن الغذائي ضمن سياسات التصدي للجائحة والإجراءات المتبعة بهذا الصدد بغية الحفاظ على الاستقرار، اذ شكلت دينامكيات الازمة تهديدا واضحا لمقومات الامن الغذائي نظرا لطبيعتها الحادة التي خلفت تأثيرات اقتصادية واجتماعية وأمنية مختلفة، انعكست سلبا على عاملي التوفر و الاستهلاك المحددين لقدرة الدول على ضمان تلبية احتياجاتها بشكل مستقر و متوازن، وتعمل الجزائر على تحقيق الاكتفاء الذاتي حيث جاءت الازمة لتختبر قدراتها على تكييف الاستجابة للتحديات الاستثنائية مع تجسيد الطموحات المتعلقة بعصرنة الاقتصاد وتطوير الإنتاج الوطني، وللحفاظ على الأمن الغذائي خلال أزمة كوفيد-19 تضمنت التجربة الجزائرية إجراءات مثل مكافحة ظاهرة المضاربة غير المشروعة ودعم قابلية الاستهلاك لضمان حصول السكان على احتياجاتهم في ظل الأوضاع الصعبة التي فرضتها الجائحة ، وهي تشكل معطيات قيمة لولوج آفاق المستقبل.
Keywords: أزمة كوفيد-19; الاكتفاء الذاتي; Food Security; Covid-19 Crisis; Economic impacts; Algerian experience; Self-sufficiency